Improving charging scheduling of public transport electric buses - Bamberg,Franz; Hassler,Anna (2023)
Title: Improving charging scheduling of public transport electric buses Authors: Anna Hassler & Franz Bamberg Supervisor: Johan Marklund, Lund University Background: This thesis focuses on a Swedish BTO that operates EB fleets. For companies investing in electrification, record-high and volatile electricity prices, present challenges and creates a need to improve the charging scheduling of EBs to reduce costs. Currently, the case company does not consider electricity prices and peak load costs in their charging scheduling. Purpose: The purpose of thesis is to investigate if there are simple and impactful changes to the charging schedule of buses at the case company that can reduce charging costs and/or decrease the stress on the grid. Methodology: The thesis follows a problem-solving approach using a modified operations research framework. Data, both quantitative and qualitative, was collected to understand the problem. Based on this data, a heuristic scheduling model was developed and evaluated using historical electricity prices and energy consumption data. Additionally, the potential of installing a battery energy storage system was studied. Conclusions: Operations and technical limitations of the case company were considered, and simple changes to the charging schedule with the purpose of reducing charging costs, were identified. The strategy involves shifting charging sessions from daytime to nighttime to reduce electricity trading costs. The results when testing the model on the month of January in 2023, however, were a total cost difference close to zero due to a drastic increase in peak load cost. Sensitivity analyses showed promising savings under specific conditions, such as using the model during summer months or periods of higher spot price volatility, increasing charging duration, lowering power output of chargers, splitting charging sessions into separate groups in the evening, or implementing a peak power ceiling. The application of a battery energy storage system of 1 MWh was also investigated and the strategy was to utilize cheaper electricity trading hours. Savings of around 448,000 SEK were found over a year for the largest depot. However, a payback period of 17.9 years limited the feasibility of the investment considering the contract lengths of around 8-10 years for BTOs.
Keywords: Peak load; electricity trading; spot prices; electric buses; bus transport operator; battery energy storage system; charging scheduling